Penerapan Metode Diskusi untuk Meningkatkan Keterampilan Siswa Kelas V SD Negeri 111 Pekanbaru - Theresia, Mariana Theresia Mariana; Kurniaman, Otang Kurniaman Otang; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research was carried out starting from still many students who do not achieve mastery of skills speaking, the number of unskilled students with 26 students or 72.22% while students who are skilled only about 10 students, or 27.73%. The problem of this research is the application of the discussion method can improve speaking skills fifth grade students of SDN 111 Pekanbaru ?. The purpose of this research is to improve students' speaking skills by applying the method in a class discussion SDN 111 Pekanbaru. This research method uses classroom action research (PTK) by applying the method in a class discussion SDN 111 Pekanbaru with the number of students 36. This action is done in November 2012 speaking skills obtained from the initial data is 49.13 by 27.73% or 10 students who skillfully obtain the minimum value. After a discussion of the method applied in the first cycle UH I, gained an average of 64.75 students' speaking skills or completeness is 75.00% or 27 students. Cycle II uh II increased to 84.72% with 97.22 completeness or 35 students. Based on these results it is concluded that the application of the discussion method can improve speaking skills fifth grade students of SDN 111 Pekanbaru with satisfactory results. Keywords : Method Discussion, Speaking Skills